Transformasi Sekolah Dasar sebagai Ruang Progresif untuk Mewujudkan Pendidikan Berbasis Nilai-Nilai Positif - Wildan Farih Kurniawan; Muhammad Aunur Rofiq; Anna Mariyani; Ayuni Rizki Amalia (Nur Science Institute, 2025)
Background: This study aims to explore how elementary schools in Blora Regency develop a values-based educational culture oriented toward students’ character formation. Method: This study employed a qualitative case study design to gain an in-depth understanding of school transformation as a progressive educational space. Data were collected through classroom observations, in-depth interviews, and document analysis involving the principal, teachers, students, administrative staff, and parents/school committee members as research participants. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The trustworthiness of the findings was established through source, method, and time triangulation. Result: The findings demonstrate that transforming schools into progressive educational spaces is achieved through strengthening school culture, transformational school leadership, instructional practices that integrate positive values, and the cultivation of positive character through everyday school routines. Core values, including honesty, discipline, empathy, responsibility, and collaboration, were fostered through strong partnerships among the school, families, and the wider community. Although several challenges were identified, such as limited facilities, varying levels of teacher readiness, and resistance to change, the shared commitment of all school stakeholders emerged as the primary factor supporting the successful implementation of values-based education. Implication: The findings provide practical guidance for schools and policymakers in strengthening sustainable, values-based character education. Novelty: This study offers an integrative school-ecosystem model for developing progressive education grounded in positive values.